The Effect of Self-Efficacy and Peers on Student Time Management Skills - Syidad, Ahmad Wildan; Julaihah, Umi (Universitas Negeri Surabaya, 2025)
Background: Students living in the Ma'had environment must face challenges in determining the scale of priorities due to the density of academic, religious and social activities. Therefore, time management skills are needed to overcome this. Objective: This study aims to analyze the influence of self-efficacy and peers on the time management skills of Mahasantri. Method: This study uses a quantitative approach with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method to analyze data from 278 respondents selected using the simple random sampling technique. Results: The results of the study showed that self-efficacy has a significant and dominant influence on time management skills, while peers have a positive but weaker influence. In addition, self-efficacy also acts as a mediator that strengthens the relationship between peers and time management. Conclusion: This study shows that individuals with high levels of self-efficacy are more able to manage time effectively. The implication of this study is the importance of improving students' self-efficacy through mastery experience programs and group guidance to strengthen social support from peers. Keywords: Mahasantri; peers; self-efficacy; time management. Abstrak Latar Belakang: Mahasantri yang tinggal di lingkungan Ma’had harus menghadapi tantangan dalam menentukan skala prioritas akibat padatnya aktivitas akademik, keagamaan, dan sosial. Oleh karena itu dibutuhkan keterampilan manajemen waktu dalam mengatasi hal tersebut. Tujuan: Penelitian ini bertujuan untuk menganalisis pengaruh self-efficacy dan teman sebaya terhadap keterampilan manajemen waktu Mahasantri. Metode: Penelitian ini menggunakan pendekatan kuantitatif dengan metode Structural Equation Modeling-Partial Least Squares (SEM-PLS) untuk menganalisis data dari 278 responden yang dipilih menggunakan teknik simple random sampling. Hasil: Hasil penelitian menunjukkan bahwa self-efficacy memiliki pengaruh signifikan dan dominan terhadap keterampilan manajemen waktu, sedangkan teman sebaya memberikan pengaruh positif tetapi lebih lemah. Selain itu, self-efficacy juga berperan sebagai mediator yang memperkuat hubungan antara teman sebaya dan manajemen waktu. Simpulan: Studi ini menunjukkan bahwa individu dengan tingkat efikasi diri yang tinggi lebih mampu mengelola waktu secara efektif. Implikasi dari penelitian ini adalah pentingnya meningkatkan efikasi diri siswa melalui program pengalaman penguasaan dan bimbingan kelompok untuk memperkuat dukungan sosial dari teman sebaya. Kata Kunci: Efikasi diri; mahasantri; manajemen waktu; teman sebaya.